Multiple antiviral mechanisms of Ephedrae Herba and Cinnamomi Cortex against influenza: inhibition of entry and replication - Aya Fujikane; Ryosuke Fujikane; Yusuke Sechi; Akinori Nishi; Yoshizumi Ishino; Tetsuya Hiyoshi; Atsuhiko Sakamoto; Shigeki Nabeshima (Microbiology Spectrum)
ABSTRACT Maoto, a traditional herbal medicine widely prescribed in Japan, has been shown to be effective in the treatment of influenza virus infection, but the mechanisms of its antiviral action remain unclear. We previously demonstrated that maoto binds to respiratory syncytial virus (RSV) spike proteins, thereby inhibiting their entry into host cells. In this report, a similar experiment was done to determine if maoto and its components have an anti-infective effect on the influenza virus. Our results indicate that maoto binds to the hemagglutinin (HA) spike protein, inhibiting virus entry into host cells in a manner analogous to its antiviral effect on RSV. This hemagglutinin-binding effect was observed across influenza A(H1N1), A(H3N2), and B viruses, highlighting the broad-spectrum inhibitory potential of maoto against diverse viral strains. Furthermore, maoto, internalized by cells along with the influenza virus, binds to a cap-dependent endonuclease (polymerase acidic [PA] protein) that is crucial for viral replication and inhibits its nuclease activity. Among maoto’s constituent crude drugs, Ephedrae Herba (EH) and Cinnamomi Cortex (CC) were found to bind to both hemagglutinin and PA, indicating that they are responsible for the anti-infective effect of maoto. Maoto is distinctive in its multiple points of antiviral action, exhibiting a broad spectrum of antiviral properties, which makes it a versatile therapeutic agent against various viral mutations.IMPORTANCEThe influenza virus is a formidable pathogen responsible for global pandemics that claim over 300,000 lives annually. Employing an ingenious evolutionary strategy, this virus undergoes constant mutation, deftly evading the action of therapeutic agents and sustaining its relentless impact. Maoto, a traditional herbal medicine, has long been known for its efficacy against viral infections and is frequently prescribed in Japan for the treatment of influenza; however, the precise mechanisms of its action remain unclear. Our study was done to elucidate the antiviral mechanisms of maoto against the influenza virus, presenting data that supports its unique potential as a therapeutic agent capable of flexibly adapting to mutations of the influenza virus. These findings pave the way for the development of new drugs and the expansion of therapeutic options.